Patterns of participation in farmers' research groups: lessons from the highlands of Southwestern Uganda - Sanginga, Pascal C.; Tumwine, Jackson K.; Lilja, N. (Springer, 2006)
There is increasing interest in farmers organizations as an effective approach to farmer participatory research (FPR). Using data from an empirical study of farmers research groups (FRGs) in Uganda, this paper examines the patterns of participation in groups and answers questions such as: Who participates? What types of participation? How does participation occur? What are the factors determining participation? Results show that there is no single type of participation, but rather that FPR is a dynamic process with types of participation varying at different stages of the process. Farmers participation does not follow the normal adoption curve. Rather, it is characterized by high participation at the initial stages, followed by dramatic decrease and dropping-out, and slow increases toward the end. There is usually significantly higher participation among male farmers at the beginning of the process. However, as FRGs evolve, the proportion of men decreases sharply while the relative proportion of women continues to increase until it dominates the group. The findings do not support the common assumption that groups usually exclude women and the poor. On the contrary, we argue that FRGs are an effective mechanism to provide women and the poor with opportunities to participate in research. However, to be effective, this requires moving beyond head counting to promote more proactive gender and equity perspectives for amplifying the benefits of agricultural research to those who tend to be marginalized or excluded by mainstream development initiatives. This will be critical for making agricultural research more client-oriented and demand-driven.